From the Critique of Healthism to a renewed Idea of the Right to Health - Gasparini, Gianluca (Soft Power, 2024)
The volume by Rosaria Pirosa, the tenth of the series “Social practice and legal theory” directed by Thomas Casadei and Gianfrancesco Zanetti, leads to the contemporary debate concerning the relationship between bioethics and law: more specifically, it focuses on the specific political implications and juridical aspects linked to healthism, as a technique of neo-governmental power.